Republic of Slovenia : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Republic of Slovenia. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2019)
This Article IV Consultation highlights that the continued structural reforms are key to ensure long-term prosperity, while strengthening the economy's resilience to shocks. Effective implementation of the recently enacted reforms of vocational training, apprenticeship, and adult education would help address skill shortages, support employment of younger and older people, and boost productivity growth. Macro-financial legacy issues remain in bank and corporate balance sheets, including small and medium enterprises' nonperforming loans. Structural challenges persist with low productivity growth, skills shortages, high tax wedge, heavy regulatory system, and extensive presence of state-owned enterprises. Policies should focus on fiscal and structural reforms to rebuild fiscal buffers and increase productivity. Slovenia's external position in 2018 is assessed as substantially stronger than suggested by fundamentals and desirable policies; however the current account is expected to revert toward its norm in the medium term. Continued structural reforms are key to ensure long-term prosperity, while strengthening the economy's resilience to shocks. Effective implementation of the recently enacted reforms of vocational training, apprenticeship, and adult education would help address skill shortages, support employment of younger and older people, and boost productivity growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet